THE NEW DEVELOPMENTS OF THE SINO-ITALIAN ECONOMIC PARTNERSHIP AFTER MARCH 2019 - Petrillo, Melania (PEOPLE: International Journal of Social Sciences, 2020)
In March 2019 China and Italy signed nineteen deals stated in the Memorandum of Understanding, that set off a new era for the Sino Italian economic partnership. Italy joined the “Belt and Road Initiative” the infrastructure maxi plan of the People’s Republic of China, which includes ports, railway lines, roads, and maritime corridors. The present research can fill a chronological gap of the relationship found in some of the previous academic works, pondering the progress in different fields during the current century: infrastructures, economy, culture, education, science and technology, innovation, society, military, arts, fashion, food, and tourism. The latest advancement of the China-Italy economic partnership is examined through the cross-national comparative method and the discourse analysis, exploring the benefits and the advantages for both countries. The author has begun to collect data from governmental sources and from the most relevant newspapers of Italy, China, Europe, the United States, to monitor the development of events related to the signature of the MOU between Beijing and Rome. It is concluded that China and Italy will maintain a long and strong bilateral partnership over the years by the constant dialogue and cooperation of the institutions. This research demonstrates the results of this win-win bilateral partnership and the benefits that both countries are perceiving.